Identifikasi Molekuler Tobacco mosaic virus pada Anggrek di Sleman, Yogyakarta - Soesamto Somowiyarjo; Sedyo Hartono; Sri Sulandari; Sekar Utami Putri (The Indonesian Phytopathological Society (Perhimpunan Fitopatologi Indonesia), 2016)
Tobamovirus is a group of virus with a wide host range, including orchid plant which considered as an economically important plant. This research aimed to identify Tobamovirus infecting orchids. Virus isolates were collected from orchid nursery in Sleman, Yogyakarta. Plant extract from orchid showing necrotic flex symptom was inoculated to indicator plants Chenopodium amaranticolor. Chlorotic local lesion symptoms occurred within 3 days after inoculation. RNA total from symptomatic C. amaranticolor was extracted by using a commercial kit. cDNA was synthesized using oligo d(T) primer. Amplification of cDNA using partial movement protein specific primers TMV-1F and TMV-2R was successfully amplified the amplicon with size ± 422 bp. The nucleotide sequences of this amplicon showed highest DNA homology (98%) with Tobacco mosaic virus Yongren-2 isolat from China.